197 miRNA-22 Regulates Vascular Smooth Muscle Cell Functions and Prevents Neointima Formation by Targeting EVI-1. (3rd June 2016) - Yang, Feng; Xiao, Qingzhong
Abstract : Background/objective: We have recently reported that microRNA-22 (miR-22) regulates vascular smooth muscle cell (VSMC) differentiation from stem cells in vitro and in vivo . However, little is known about the functional involvements of miR-22 in VSMC functions and vessel injury-induced neointima formation. In the current study, we aimed to establish the causal role of miR-22 and its target genes in VSMC proliferation, migration and neointima lesion formation. Methods and results: miR-22 was significantly down-regulated in VSMCs upon various pathological stimuli, and in injured arteries. miR-22 over-expression in serum-starved VSMCs significantly inhibited VSMC proliferation and migration, while knockdown of miR-22 dramatically promoted VSMC proliferation and migration, respectively. Ecotropic virus integration site 1 protein homolog (EVI-1), a transcription factor localised to the nucleus and binds DNA through specific conserved sequences of GACAAGATA with the potential to interact with both corepressors and coactivators, was predicted as one of the top targets of miR-22 by using several computational miRNA target prediction tools, and was negatively regulated by miR-22 in VSMCs. The luciferase activity of the wild-type, but not the miR-22 binding site mutants of EVI-1 3’-UTR reporter was substantially repressed by miR-22 overexpression, confirming the EVI-1 is one of the functional targets of miR-22 in VSMCs. Data from co-transfection experiments also revealed that miR-22 inhibited VSMC proliferation and migration through repressing EVI-1 gene expression. Importantly, perivascular enforced expression of miR-22 in the injured vessels significantly reduced EVI-1 expression levels, decreased VSMC proliferation, and inhibited neointima formation in wire-injured femoral arteries. Conclusions/implications: Our data have demonstrated that miR-22 is an important regulator in VSMC functions and neointima hyperplasia, suggesting its potential therapeutic application for vascular diseases.